Human epidermal growth factor receptor 2 neu and E-cadherin expression in primary astrocytic brain tumors as prognostic biomarkers - Mohamed Y Ali; Marwa A El Kholy (Wolters Kluwer Medknow Publications, 2021)
Background The primary brain tumors including astrocytic tumors, ranging from circumscribed into diffuse and glioblastoma (GBM), which is considered as a highly malignant neoplasm of the central nervous system. They share common molecular and biological abnormalities. This study was aiming to illustrate the role of c-erbB-2 protein [human epidermal growth factor receptor 2 (HER2 neu)] and E-cadherin expression in varied groups of astrocytic tumors. Patients and methods The material of this work consisted of 50 cases with histopathological diagnosis of astrocytoma and GBM. The patients were classified histopathologically into four grades based on the WHO 2007 criteria: pilocytic astrocytoma (G1), diffuse astrocytoma (G2), anaplastic astrocytoma (G3), and GBMs (G4). C-erbB-2 protein and E-cadherin expressions were estimated semiquantitatively on immunohistochemically tissue sections stained with antibodies against c-erbB-2 protein and E-cadherin. Results Checking HER2 scores, 29 (58%) cases were HER2 neu positive. Comparing the percentage of all cases of astrocytic tumors, it was found that the most obvious positive staining was observed predominantly in anaplastic astrocytoma and GBM cases. Regarding E-cadherin, 19/50 (38%) cases were E-cadherin positive with variable expressions moderate to strong immunostaining, but was typically higher in low-grade astrocytoma than in higher grades. Conclusions Taken together from our and other data, HER2 overexpression may be considered a poor prognostic marker in patients with astrocytic tumors of the brain especially GBM and cadherin cell-cell contacts in astrocytoma cells may decrease its invasion, and they could become a new potential therapeutic strategy for astrocytoma's treatment.